(untitled) (World Bulletin of Social Sciences, 2024)
It is no exaggeration to say that today we cannot imagine our life without advertising. The reason is that the demand for food products of almost all the world’s population is increasing day by day. Therefore, in order to increase the demand of consumers for food products, great importance is attached to advertising. Due to the influence of advertising, it is natural for manufacturing organizations to turn to advertising to increase the demand for their products or to demonstrate this product. In this article, in fact, what is advertising, and the theoretical basis of the gastarnomic advertising text, are discussed more widely.